Differentiated Learning: Teachers' Understanding of Sekolah Penggerak Program at Deli Serdang District North Sumatera - Ricu Sidiq; N Najuah; S Syarifah (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research aims to describe the level of understanding of secondary school teachers in the Deli Serdang area regarding differentiated learning in the Independent Curriculum that applies in Indonesia. This research is quantitative survey research. Population: The subjects of this research were high school teachers in Deli Serdang Regency, totalling 366 people, with a sample of 216 people selected by random sampling. Data was collected through a survey using a closed questionnaire. The data analysis technique uses the Mann-Whitney test to see differences in teachers' understanding of differentiated learning in public and private schools participating in the Driving School Program. The research results show that the level of teacher understanding of differentiated learning in private schools is moderate, and the level of understanding of teachers in state schools is in the high category. Based on the Driving School Program, which does not differentiate between the status of public and private schools in funding and program assistance, differences in understanding occur due to several internal and external factors found in schools, such as principal leadership, teacher competency, and different teacher statuses in the two types of schools. In conclusion, the Mobilizing School Program provides the same treatment in public and private schools and has the same programs and assistance. However, teachers' understanding of learning varies, which certainly impacts the learning process and learning outcomes.